ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN MELALUI MINAT BELI KONSUMEN SEBAGAI VARIABEL INTERVENING PADA WARUNG TAHU TEK CAK SUGENG DI SITUBONDO - Irfan, Mohammad Zidni; Arief, Mohammad Yahya; Soeliha, Siti (Fakultas Ekonomi dan Bisnis, 2023)
The culinary business is the choice of many people because this type of business is easier to run than other businesses. The large number of culinary business actors who open restaurant businesses has resulted in a high level of competition between culinary business actors. The easy system makes many people use this service as an alternative choice to get food in an easy way. The purpose of this study is to determine the factors that influence customer satisfaction through consumer buying interest as an intervening variable at Warung Tahu Tek Cak Sugeng Situbondo. the population in this study is the entire population in this study are all consumers who make purchases at Warung Tahu Tek Cak Sugeng Situbondo. After observing and interviewing consumers, Warung Tahu Tek Cak Sugeng Situbondo. Random sampling method (simple probability sampling) without regard to strata in the population in this study. Data analysis and hypothesis testing in this study used the Structural-partial Least square equation model (PLS-SEM). The results of the hypothesis test have a direct effect using the smart PLS 3.0 application, indicating that price has a significant positive effect on purchase intention. Service quality has a significant positive effect on purchase intention. Price has a significant negative effect on customer satisfaction. Service quality has a significant positive effect on customer satisfaction. Purchase intention has a significant positive effect on customer satisfaction. Price has a significant positive effect on customer satisfaction through purchase intention. Service quality has a significant positive effect on customer satisfaction through purchase intention.